The role of school governing bodies in transforming education in South Africa : a study of selected secondary schools in the Tsomo district of Eastern Cape Province - Mkentane, Mziwamadoda Anderson (Stellenbosch : Stellenbosch University, 2012)
Thesis (MEd)--Stellenbosch University, 2003.